2013
DOI: 10.2174/18722148113079990011
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Oxidant Properties of Isothiocyanates: A Review

Abstract: Cruciferous vegetables, such as broccoli and watercress, have been studied extensively aiming to evaluate their chemopreventive properties. Some of them have already been established using animal models. The ITCs induce Phase II enzymes related to detoxification processes of chemical carcinogens to prevent the start of carcinogenesis. They also exhibit antitumor activity at post-initiation phase, suggesting their additional role(s) in cancer prevention. Sulforaphane is the most extensively studied isothiocyana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 53 publications
0
20
1
2
Order By: Relevance
“…Isothiocyanates, a group of natural bioactive compounds mostly present in cruciferous vegetables, are characterized by their antioxidant properties [ 148 ]. That is what enabled them to be used in the alleviation of platinum drug-induced neurotoxicity.…”
Section: Antioxidants In the Treatment Of Platinum-based Chemothermentioning
confidence: 99%
“…Isothiocyanates, a group of natural bioactive compounds mostly present in cruciferous vegetables, are characterized by their antioxidant properties [ 148 ]. That is what enabled them to be used in the alleviation of platinum drug-induced neurotoxicity.…”
Section: Antioxidants In the Treatment Of Platinum-based Chemothermentioning
confidence: 99%
“…Furthermore, phenethyl isothiocyanate had inhibitory activity against liver cancer induction by N-nitrosodiethylamine in the mice (19). Studies developed in vitro have also demonstrated that ITCs induce apoptosis, which could be linked to their chemopreventive activity in the postinitiation phase (10). Sulforaphane, one of the most extensively studied ITCs, may have a potential effect on decreasing the secretion of inflammatory signaling molecules by white blood cells and DNA binding of nuclear factor-kappa B (NF-κB), which is one of the early key events involved in neoplastic progression of the liver (21-23).…”
Section: Discussionmentioning
confidence: 99%
“…Sulforaphane, one of the most extensively studied ITCs, may have a potential effect on decreasing the secretion of inflammatory signaling molecules by white blood cells and DNA binding of nuclear factor-kappa B (NF-κB), which is one of the early key events involved in neoplastic progression of the liver (21-23). Furthermore, several studies have suggested that IκB kinase complex inhibition and/or signal transducer and activator of transcription 3 downregulation may attribute to ITCs-induced apoptosis (10, 34). Although ITCs are metabolized and disposed in a time-dependent fashion, total urinary ITCs levels was still considered as the best biomarker of human exposure to dietary ITCs recently (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Su efecto antinflamatorio, ha sido observado en consumidores crónicos de maca, en los cuales se encontraron niveles más bajos de IL6 [74]. Algunos de sus principios activos están relacionados a otras especies de lepidium como la mostaza, el nabo, col, berros [76], brócoli, reconocidos por sus propiedades preventivas, asociados al contenido de isotiocianatos [92], que a dosis dependiente, inducen la reducción de la expresión de IL1β, TNFα, IL6, óxido nítrico a través de sON y enzimas COX 2 asociadas a la producción de citoquinas proinflamatorias [92]. Los isotiocianatos dietarios son eficientemente absorbidos (≥80%), pero aún se requieren estudios respecto a su bioactividad [93].…”
Section: Referencia Bibliográficaunclassified